2021
DOI: 10.3390/microbiolres12040071
|View full text |Cite
|
Sign up to set email alerts
|

Potential Associations of Mutations within the HIV-1 Env and Gag Genes Conferring Protease Inhibitor (PI) Drug Resistance

Abstract: An increasing number of patients in Africa are experiencing virological failure on a second-line antiretroviral protease inhibitor (PI)-containing regimen, even without resistance-associated mutations in the protease region, suggesting a potential role of other genes in PI resistance. Here, we investigated the prevalence of mutations associated with Lopinavir/Ritonavir (LPV/r) failure in the Envelope gene and the possible coevolution with mutations within the Gag-protease (gag-PR) region. Env and Gag-PR sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 42 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…From the structural changes observed in Gag, the Q69K that was previously reported to coevolve with gp120 and minor protease mutations (Codoñer et al, 2017;Maphumulo and Gordon, 2021), showed a longer α-4/5 loop than the WT. This position has been reported to contribute to the structural flexibility of MA and the longer loop seen in the mutant suggests that it occupied more volume than the WT (Khan and Vihinen, 2007).…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…From the structural changes observed in Gag, the Q69K that was previously reported to coevolve with gp120 and minor protease mutations (Codoñer et al, 2017;Maphumulo and Gordon, 2021), showed a longer α-4/5 loop than the WT. This position has been reported to contribute to the structural flexibility of MA and the longer loop seen in the mutant suggests that it occupied more volume than the WT (Khan and Vihinen, 2007).…”
Section: Discussionmentioning
confidence: 85%
“…Env gp41 mutations associated with PI treatment failure that have been previously reported were found in the Ectodomain (I515L, S543A,T536M, A607T, D632E, and L641), Transmembrane (I688V), and cytoplasmic tail (CT) (L721I, P724S, I781T, T818, V832I, and I/ L836F) (Coetzer et al, 2017;Manasa et al, 2017;Castain et al, 2019;Perrier et al, 2019;Maphumulo and Gordon, 2021). The N-terminal HR and C-terminal HR regions are located in an antiparallel orientation and are linked by a loop region that plays a critical role in fusion (Bär and Alizon, 2004).…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations